DOCUMENTING THE IMPACT OF SOCIOECONOMIC DYNAMICS ON HERITAGE SITES. THE CASE OF VISTA ALEGRE DISTRICT IN SANTIAGO DE CUBA - L. B. Caballero; M. M. Castillo; K. Van Balen (ISPRS Annals of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2017)
Recent policies adopted in Cuba are producing a significant turn into the country’s socioeconomic dynamics. Past shifting circumstances have demonstrated the positive and negative implications on heritage sites. In this regard, this paper presents a first stage of a research project aimed at monitoring the impact of socioeconomic dynamics on local heritage sites. The research partial results focus on the documentation of the evolution of a case study: Vista Alegre District in the city of Santiago de Cuba. Scholars have noted that the District’s urban design and historic building stock represent its most significant heritage values. Such qualities are under permanent threat due to transformations and deterioration. In order to analyse current site condition, and to understand transformations as a result of socioeconomic dynamics, a Geographic Information System (GIS) was implemented as a monitoring and documenting tool. The GIS allowed integrating data related to the evolution of the urban layout, and the heritage buildings. Data was sourced from heritage management and urban planning offices, as well as from previous studies on the site. In addition, the analysis of remote sensing imagery, and a field survey helped to update the existing records, and to include new information with the purpose of assessing the integrity of heritage values. At this stage, maps that describe the site evolution, the significant changes over time, and the alterations to character defining elements served to identify sectors of different scenic qualities. Results are essential to contribute to draft management strategies as part of decision making.